2015
DOI: 10.1007/s13187-015-0838-8
|View full text |Cite
|
Sign up to set email alerts
|

Tweeting About Prostate and Testicular Cancers: What Are Individuals Saying in Their Discussions About the 2013 Movember Canada Campaign?

Abstract: Effective and persuasive health campaigns are an important tool for promoting cancer prevention education. The 2013 Movember Canada campaign presented an opportunity to raise awareness and funds about men's health with a particular focus on prostate and testicular cancers. The Movember campaign encouraged participants to talk about men's health (including prostate and testicular cancers) and had a strong presence on social media sites such as Twitter in November 2013. The objective of this study was to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…This is a free application that allows easy access to 1% of all Twitter data in real time, filtered by specific criteria (eg, keywords) [ 76 , 77 ]. Lastly, SM can be directly used by health researchers to support prevention interventions to raise awareness and engage populations [ 78 ] and to crowdfund by promoting their research on SM. Indeed, crowdfunding can be eased by establishing professional contacts through SM and sharing campaigns [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is a free application that allows easy access to 1% of all Twitter data in real time, filtered by specific criteria (eg, keywords) [ 76 , 77 ]. Lastly, SM can be directly used by health researchers to support prevention interventions to raise awareness and engage populations [ 78 ] and to crowdfund by promoting their research on SM. Indeed, crowdfunding can be eased by establishing professional contacts through SM and sharing campaigns [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, content produced for social media-based campaigns can be unrelated to the campaign’s target. For example, it was found that the majority of Movember campaign-related tweets did not associate with prostatic and testicular cancer awareness [ 39 ], and the majority of tweets produced during breast cancer awareness week did not promote any specific preventive behaviors [ 40 ]. Despite the importance of developing related content, research into the correlation between social media-based awareness campaigns and behavior change is minimal because it is a new avenue in public health awareness [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to this, content on social media is interactive, where patients and caregivers are able to obtain information while also contributing to a networked process of content development and diffusion (Chou et al, ). Recent research documents that patients and their caregivers use social media as a way to share their illness experiences (Gage, ; Gomez‐Zuniga et al, ; Chou et al, ; Clerici et al, ; Greene et al, ; Greaves et al, 2013; Wicks et al, 2013) and engage in health‐related discussion (Bravo & Hoffman‐Goetz, ; Chou, Prestin, & Kunath, ; Tsuya et al, ).…”
Section: Introductionmentioning
confidence: 99%